Trauma-Associated Sleep Disturbances: a Distinct Sleep Disorder? - Rachakonda, Tara D. (Curr Sleep Med Rep, 2018)
PURPOSE OF REVIEW: This paper describes a newly proposed sleep disorder, trauma-associated sleep disorder (TSD). Whether or not this represents a truly unique condition is controversial. In this paper, we describe the overlapping features and differences between TSD, post-traumatic stress disorder (PTSD) and Rapid Eye Movement (REM) sleep behavior disorder (RBD). RECENT FINDINGS: While REM sleep without atonia (RWA) and dream enactment are part of the diagnostic criteria for both RBD and TSD, only TSD features nightmares that occur both in non-REM and REM. A key difference between TSD and PTSD is the presence of symptoms during wakefulness in the latter, though the relationship between the two disorders is, as of yet, unclear. It is unknown whether or not a relationship exists between TSD and neurodegeneration, thus this needs to be explored further. SUMMARY: Additional research, such as application of TSD diagnostic criteria to more diverse population, would help to determine whether or not TSD is a distinct clinical entity, its relationships to PTSD, as well as the association of this condition with the development of neurodegeneration.